The impact of exercise intensity on depression in fibromyalgia: a randomized controlled trial - Vilarino, Guilherme Torres; Coimbra, Danilo Reis; Neiva, Henrique Pereira; Andrade, Alexandro (Frontiers in Psychology, 2024)
Background: Fibromyalgia (FM) is characterized by widespread chronic pain. Although pain is the main symptom, approximately 90% of patients have depression. This study aimed to analyze the effects of Resistance Training (RT) with low and high intensity on depression in patients with FM. Methods: Thirty-eight women with FM and 31 healthy women were allocated to the low-intensity, high-intensity, preferred-intensity, and control groups. The patients underwent eight weeks of supervised RT, with two sessions per week of approximately one hour. The low-intensity resistance training group (LIRT) performed two sets of 12 maximum repetitions. The high-intensity resistance training group (HIRT) performed four sets with six maximum repetitions, and the preferred intensity group (PI) performed three sets, with eight to 12 repetitions, according to the patient's tolerance. The healthy control group did not perform any type of exercise. Depression was assessed using the Beck depression inventory before the start of the intervention, after 4 and 8 weeks. Results: FM patients have higher levels of depression than women without the disease. After 4 weeks, there was a difference in depressive symptoms between the HIRT and LIRT (p = 0.048), and the PI and LIRT (p = 0.048). Conclusion: Prescribing RT with low or high intensity did not significantly reduce depression in patients with FM after 8 weeks, however, analyses between groups after 4 weeks indicated that low-intensity training is more effective than high-intensity training. The prescription of RT exercise to FM could vary among low, high, and preferred intensity, following the patient’s tolerance for pain. Trial registration: The research was registered in the Brazilian Registry of Clinical Trials (no. RBR-74pcmw - https://ensaiosclinicos.gov.br/rg/RBR-74pcmw)